Забезпечення книгами людей з вадами зору: аналіз українського видавничого ринку 2010-2015 рр. - Hrynivskyi, Taras; Kopystynska, Iryna (Київський національний університет культури і мистецтв, 2018)
У статті розглянуто стан вітчизняного книгодрукування для людей з вадами зору за період 2010–2015 рр. Окреслено потенційну читацьку аудиторію, визначено потребу й ступінь забезпечення відповідною друкованою продукцією. Наголошено на тому, що оскільки швидкість зношеності таких видань дуже висока, то перш за все варто поповнювати фонди спеціалізованих шкіл підручниками та художньою літературою шрифтом Брайля, книгами збільшеного шрифту для слабозорих дітей, аудіо- та тактильними книгами. Наступний крок — поповнення фондів спеціалізованих бібліотек, а також бібліотек загального користування. На сьогодні чи не єдиною установою, яка може друкувати такі видання в Україні, є Республіканський будинок звукозапису й друку УТоС. Його потужності здатні повністю забезпечити наявний попит, проте на це потрібне відповідне фінансування, якого немає. У статті наголошується, що собівартість таких книг досить висока, а тому основне фінансове навантаження повинна взяти на себе держава як у всьому цивілізованому світі. Натомість в українських реаліях, навіть попри певні позитивні зрушення, зокрема, й на законодавчому рівні (постанови Кабінету Міністрів України), — це поки що ініціатива окремих активістів, громадських організацій, видавництв. The article deals with the situation in the national publishing market for people with weak eyesight in the period 2010–2015. The potential readers audience, essential needs and the degree of necessary published products provision are analyzed. As the process of such publications deterioration is short, it is important to replenish specialized school funds with textbooks and literary works, printed in Brialle print, books with enlarged print for weak eyesight people, audio and tactile books. This is a burning problem as the provision of such schools with textbooks is only 15–42%. Such literature should be published in small numbers — 100–200 copies of each title, but it would give the possibility to provide such institutions with the necessary number of textbooks. The next, but not less important move is the replenishment of both — specialized libraries and libraries of common use with literature for people with eyesight problems. For example, in Chernivtsi libraries — either in university scientific one, or in city and regional ones — expedient funds are either absent or very small in number. M. Ostovskyi central specialized library for blind people is the largest library with appropriate funds in Ukraine. Today almost the only organization which can print the above mentioned specialized publications in Ukraine is Republican House of sound recording and printing UPofB (Ukrainian Partnership of Blind), its production capacities can fully provide the exis ting demand, but it needs financing, which is absent. The cost price of such books is rather high, that is why the principle financing should be provided by the state, as well as in the rest of civilized world. Instead, notwithstanding certain positive changes, including the legislative level (Decision of the Cabinet of Ministers of Ukraine), it is still the initiative of only some activists, social organizations, publishing houses.
BOOKS PROVISION OF PEOPLE WITH VISUAL IMPAIRMENTS: THE ANALYSIS OF THE UKRAINIAN PUBLISHING MARKETIN 2010–2015
Keywords: видання для людей з вадами зору, шрифт Брайля, бібліотечні фонди, спеціалізовані школи, тактильні книги, аудіокниги; publications for people with eyesight problems, Brialle print, library funds, specialized school, tactile books, audiobooks